2008
DOI: 10.1007/s11746-008-1337-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Stability of Virgin Olive Oils from Some Important Cultivars in East Mediterranean Area in Turkey

Abstract: Some important olive cultivars (Kilis yaglık, Halhalı, Karamani, Haşebi, Nizip yaglık) in East Mediterranean Area were studied. Olive fruits were processed on a low-scale mill equipped with a basket centrifuge. Basic quality parameters, the content of total polyphenols, o-diphenols, oxidation stability (Rancimat) and antiradical activity [1,1-diphenyl-2-picrylhydrazyl (DPPH)] were determined in oil samples. The highest induction period (IP) was 36.42 h, found in the Halhalı cultivar (from Gaziantep province), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 17 publications
11
36
0
Order By: Relevance
“…The distribution of fatty acids in the oils of domestic cultivars was in agreement with those of authors working on Turkish olive oil varieties (Ersoy et al 2001;Dıraman and Hı7ıl 2004;Tous et al, 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009) and these values for foreign cultivars were similar to those reported for foreign olive oil varieties (Gutiérréz et al 1999;Gimeno et al 2002;Ollivier 2003;Poiana and Mincione 2004;Tous et al 2005). (Figure 2) based on their fatty acid profiles.…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
See 3 more Smart Citations
“…The distribution of fatty acids in the oils of domestic cultivars was in agreement with those of authors working on Turkish olive oil varieties (Ersoy et al 2001;Dıraman and Hı7ıl 2004;Tous et al, 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009) and these values for foreign cultivars were similar to those reported for foreign olive oil varieties (Gutiérréz et al 1999;Gimeno et al 2002;Ollivier 2003;Poiana and Mincione 2004;Tous et al 2005). (Figure 2) based on their fatty acid profiles.…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 88%
“…The linolenic acid (18:3 n-3) level of the oils from domestic and foreign cultivars was below the maximum value fixed by the IOOC (1.0%) and by the Turkish Codex and EU (0.9 %). These findings on linolenic acid are in agreement with the results found in various producing countries of the Mediterranean basin (Gutiérréz et al 1999;Ersoy et al 2001;Gimeno et al 2002;Ollivier et al 2003;Dıraman and Hı7ıl 2004;Tous et al 2005;Köseo≈lu et al 2006;Saygin and Yemi7ço≈lu 2007;Gürdeniz et al 2008;Kıralan et al 2009;Andjelkovic et al 2009). The linolenic acid levels of olive varieties, Picholine, Arbequnia, Manzanilla and Leccino, cultivated in Moorocco were higher (more 1%) than our results (Al -Antari et al 2003).…”
Section: Chemometric Classification Of Domestic and Foreign Olive Culsupporting
confidence: 87%
See 2 more Smart Citations
“…These results are in agreement with those reported by Kiralan et al (2009), they found that the high total polyphenols content increased the antioxidant activity and there was a linear correlation between phenolic content and antioxidant activity.…”
Section: Antioxidant Activity Of Virgin Olive Oilssupporting
confidence: 94%